Perceived Organizational Barriers to Women’s Career Advancement in Nepal - Thakurathi, Safalta (Nepalese Journal of Business, 2025)
The study examines the perceived organizational barriers to women’s career advancement in Nepal. Women’s career advancement is the dependent variable. The selected independent variables are glass ceiling, mentoring, networking, organizational structure, family barriers, and marital status. Primary data is used to assess the opinions of respondents regarding these organizational barriers on women’s career advancement in Nepal. The study is based on primary data collected from 150 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of these barriers on women’s career advancement in Nepal. The study revealed that the glass ceiling negatively impacts women’s career advancement in Nepal, indicating that breaking down invisible barriers and providing equal opportunities lead to higher career progression for women. Mentoring positively affects career advancement, suggesting that support and guidance from experienced mentors increase women’s career progression. Networking also plays a crucial role, with greater access to professional networks leading to higher career advancement for women. The organizational structure positively impacts career growth, indicating that supportive and inclusive organizational policies enhance women’s career progression. Additionally, family barriers and marital status significantly affect women’s career advancement, revealing that supportive family environments and flexible marital arrangements correlate with increased career opportunities for women in Nepal.